유전 알고리즘을 이용한 이동 에이전트 기반의 경로 탐색 기법 - 지홍일(Hong-il, Ji) (한국정보통신학회논문지, 2015)
Proposed algorithm in this thesis introduced cells, units of router group, to conduct distributed processing of previous genetic algorithm. This thesis presented ways to reduce search delay time of overall network through cell-based genetic algorithm. Also, through this experiment, in case of a network was damaged in existing optimal path algorithm, Dijkstra algorithm, the proposed algorithm was designed to route an alternative path and also as it has a 2nd shortest path in cells of the damaged network so it is faster than Dijkstra algorithm, The study showed that the proposal algorithm can support routing of alternative path, if Dijkstra algorithm is damaged in a network. 본 논문에서는 제안한 알고리즘은 이전 유전 알고리즘의 분산처리를 위해 라우터 그룹 단위인 셀을 도입하였다. 셀 단위로 유전 알고리즘을 시행하여 전체 네트워크의 탐색 지연시간을 줄이는 방법을 제시하였다. 또한, 실험을 통하여 기존 최적경로 알고리즘인 Dijkstra 알고리즘에서 네트워크가 손상되었을 경우 제안한 알고리즘에는 대체 경로 설정의 연산시간이 단축되었으며 손상된 네트워크의 셀 안에서 2순위의 경로를 가지고 있으므로 Dijkstra 알고리즘보다 신속하게 대체경로를 설정하도록 설계되었다. 이는 제안한 알고리즘이 네트워크상에서 Dijkstra 알고리즘이 손상되었을 경우 대체 경로설정을 보완할 수 있음을 확인하였다.